The influence of electronic word of mouth through Tiktok on purchasing intention of skincare products in Indonesia (Asian Journal of Economics and Business Management, 2022)
The ever-expanding internet has brought social media become a medium by which Electronic Word of Mouth (eWOM) is disseminated, particularly among skincare users. This study aims to assess the impact of eWOM through TikTok on skincare product purchase intention by developing a conceptual model of hypotheses that encompasses a multiplicity of factors that might be associated. The researcher investigates what factors impact eWOM usefulness & eWOM credibility and why consumers may adopt it when making a purchase. To examine our research model, a quantitative approach is employed using a sample of 373 Indonesian respondents via a web-based questionnaire. Structural equation modeling (SEM) analysis with the program SmartPLS was employed to test ten proposed hypotheses. The results indicate that source expertise is the most significant factor that may impact eWOM credibility in addition to perceived persuasiveness, perceived informativeness, and source trustworthiness. Additionally, source trustworthiness is the main predictor of eWOM credibility in addition to perceived persuasiveness and source expertise with regard to TikTok. It was found that eWOM usefulness and credibility together increase the possibility of adopting an eWOM message, and eWOM adoption mediates the influence of credibility and usefulness on customer purchase intention toward skincare products on TikTok. Only a few studies have examined TikTok as a medium of eWOM distribution and its influence on skincare product purchase intention, therefore this study provides vital insights into eWOM literature by identifying the new platform. This study helps brands learn what to consider when designing marketing strategies to enhance purchase intentions.